Pengaruh Komunikasi Pimpinan, Motivasi Kerja terhadap Kinerja ASN Dinas Peternakan Rote Ndao - Haning, Hermanus (Jurnal Informatika Ekonomi Bisnis, 2024)
This research aims to analyze the influence of leadership communication (X1) and work motivation (X2) on the performance of ASN (Y) of the Rote Ndao Regency Livestock Service. The validity test is carried out by correlating the score of each factor with the total score and is declared valid if r calculated > r table (0.266) or significance < 0.05. The results show that all items in the leadership communication, work motivation and ASN performance variables are valid. The reliability test uses Cronbach's Alpha with criteria > 0.60. The results show a value of 0.751 for leadership communication, 0.818 for work motivation, and 0.751 for ASN (State Civil Apparatus) performance, so that all variables are reliable. The regression results show that the beta coefficient of leadership communication (0.388) and work motivation (0.579) have a positive effect on ASN performance. The constant value of -2.048 shows that without these two variables, ASN performance decreases. The determination test produced an R² of 0.778, meaning that 77.8% of the variation in ASN performance was explained by leadership communication and work motivation, while 22.2% was explained by other factors. The T test shows the significance of leadership communication (0.002) and work motivation (0.000), so both are partially significant. The F test shows a significance of 0.000, meaning that both variables are simultaneously significant for ASN performance.This research concludes that leadership communication and work motivation play a significant role in improving the performance of ASN of the Rote Ndao Regency Livestock Service, both partially and simultaneously.